Evaluation of Creative Thinking Skills in the Development of Elementary Science Learning in Elementary Schools: A Mix Method Study - Yasa, Arnelia Dwi; Kumala, Farida Nur; Wibawa, Aji Prasetya; Hidayah, Laily (LPPM Undiksha, 2023)
Students' creative thinking abilities are still limited in science learning development lectures. Students are only able to answer questions at the concept application level (C1-C3 or lower order thinking skill). This is due to the lack of variety in learning methods, lecture material has not been linked to contextual problems. This research aim is to analyze the creative thinking abilities of elementary teacher education students in elementary science learning development courses. This study uses mixed method. Sampling was carried out using random sampling involving 233 students from 8 different campuses. The research instrument consists of a test that includes 12 questions related to indicators of creative thinking skills (fluency, flexibility, originality, and collaboration), semi-structured interviews with 10 respondents to explore the understanding behind the answers given, and documentation. Data analysis techniques are carried out through quantitative and qualitative data analysis which includes data reduction, data presentation, as well as drawing conclusions and verification. The research results show that of the four indicators of creative thinking, students are categorized as sufficient in the fluency aspect. However, the other three indicators, namely flexibility, originality, and elaboration are in the poor category. The interview results also revealed that the majority of respondents were unable to provide answers that were in accordance with the indicators of creative thinking achievement. The conclusion of this research is that three indicators of creative thinking, namely flexibility, originality and elaboration, need to be improved because they are categorized as lacking.